Poisonings in childhood: A 5-year experience of a tertiary city hospital in İstanbul - Mehmet Tolga Köle; Yakup Çağ; Feyza Hüsrevoğlu Esen; Hakan Günhan; Kemal Pişmişoğlu; İbrahim Kandemir; Serdar Mehmetoğlu; Aydan Erdem; Gökşen Erkin; Yasemin Akın (Trends in Pediatrics)
Objective: Poisoning is a substantial public health problem preventable with basic precautions. This study aims to contribute to the literature by analyzing the demographic variables, epidemiological characteristics, and prognosis of children brought to the pediatric emergency department of our center due to poisoning in the last five years.